A Study on Langevin Equations with ψ-Hilfer Fractional Derivative - Harikrishnan, S.; Kanagarajan, K.; Vivek, D. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we discuss the existence, uniqueness and four types of Ulam stability results for a general class of Langevin equations. An illustrate example is given tocheck the applicable of this results.